Retail distribution channel barriers to international trade - Frederic Michael Scherer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
With the referral of the Kodak - Fuji market access dispute to the World Trade Organization, the role of retail distribution channel control by incumbent firms as a barrier to imports has drawn much interest. This paper reviews the issues from an historical perspective and analyzes the difficulties facing firms attempting to sell their products in other nations' automobile and photo supplies markets. There has been a natural evolution of retail distribution channels from mom and pop stores to hyper markets. The earlier the stage in this evolutionary process at which a nation's retail channels stand, the more difficult it is for consumer goods importers to secure their own products' distribution. Volkswagen's early entry into the U.S. automobile market and Nissan's later entry are analyzed as examples of how exclusive distribution channels controlled by incumbents can be surmounted. Key aspects of the Kodak Fuji case are also examined. The advantages and disadvantages of manufacturers' restraints on their distributors are so complex, the paper concludes, that it would be difficult to adopt uniform international competition policies toward trade-impairing vertical restraints.
Keywords: 330; Nichttarifäre Handelshemmnisse; Außenhandel; Vertriebsweg; Markteintritt; Wettbewerbsbeschränkung; Kraftfahrzeug; Fotografie; Welt